Efektifitas siwak (Salvadora persica) dan pasta gigi siwak terhadap akumulasi plak gigi pada anak-anak (Effectiveness of Siwak (Salvadora persica) and siwak toothpaste on dental plaque accumulation in children) - Indra Bramanti; Iwa Sutardjo RS; Navilatul Ula; Muhammad Isa (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: siwak contain of salvadorine with an antiseptic effect. There were many reports about antibacterial effect of siwak on the cariogenic bacterial, pathogen periodontal, and dental plaque accumulation. Purpose: The study was aimed to determine the effect of siwak and siwak toothpaste on accumulated dental plaque in children. Methods: The subjects were 39 teenage children in range of age 12-15 years old, and were divided on 3 groups. Each subject group was asked to brush their teeth 3 times a day using siwak; siwak toothpaste; and toothpaste with no additional substance as control, respectively. After brushing for a week, plaque scoring was performing using Modified Personal Hygiene Performance Index (PHP-M). Data were analysed using one way Anova. Results: The plaque score on siwak group lower significantly than control group, but there was no significant difference between siwak group and siwak toothpaste group. Conclusion: The study suggested that siwak and siwak toothpaste had the same effect on decreasing plaque accumulation in children.Latar belakang: siwak mengandung salvadorine yang berefek sebagai antiseptik. siwak juga dilaporkan memiliki efek antibakteri terhadap bakteri kariogenik dan pathogen periodontal, dan menghambat pembentukan plak. Tujuan: Penelitian ini bertujuan untuk menguji efek siwak dan pasta gigi siwak terhadap akumulasi plak pada anak. Metode: subyek penelitian adalah 39 anak remaja berusia 12-15 tahun yang dibagi dalam 3 kelompok. setiap subyek dalam kelompok yang sama diminta untuk menyikat gigi sehari 3 kali dengan menggunakan siwak; pasta gigi siwak; dan pasta gigi murni tanpa tambahan bahan sebagai control. setelah selama seminggu menyikat gigi, dilakukan pengukuran skor plak menggunakan indeks PHP-M. Data yang diperoleh dianalisis menggunakan Anova satu jalur. Hasil: skor plak kelompok siwak lebih rendah secara signifikan dibanding kelompok pasta gigi murni, namun antara kelompok siwak dan pasta gigi siwak tidak terdapat perbedaan yang bermakna. Simpulan: studi ini menunjukkan bahwa siwak dan pasta gigi siwak memiliki efek yang sama dalam menurunkan akumulasi plak pada anak.